Research Trends and Gaps in Learning Environment Characteristics in Communities: A Bibliometric Analysis (2019–2024) - Hamdi, Hamdi; Santiani, Santiani; Jasiah, Jasiah; Syi'bul Huda, Ali Anhar; Mualimin, Mualimin (J-PAI: Jurnal Pendidikan Agama Islam, 2024)
Abstract. The learning atmosphere, especially in the environment, is still not optimal so that it does not have a positive impact on the learning process. The purpose of this study is to describe Research Trends and Gaps in Characteristic Learning Environment in the Community: A Bibliometric Analysis (2019–2024). The approach used is quantitative which specifically uses bibliometric analysis. Data source from Crossref, a publish or perish (PoP) application with 500 articles as a sample with the keyword characteristics of the learning environment in the community for the period 2019-2024 produced 1000 articles which were then analyzed using the VOSViewer application version 1.6.20. The results of the research on the topic of characteristics of the learning environment in the community with a span of 2019-2024 show that the ups and downs of publications seem to be decreasing in 2024. The results of the research with the most publications on the characteristics of the learning environment in the community in 2020 (27 publications). Productive researchers include Michael Cann, Gary Harfitt, Marjorie Mayo, Ntimi Mtawa, Muhammad Hassan Raza, Rachael W. Shah, and Osly Usman. Based on the source from VOSViewer, a map of research development was produced, there are 3 clusters. Cluster 1 (36 items), cluster 2 (31 items), and cluster 3 (20 items). The keywords that are widely researched include characteristic, teaching, community engagement, program, and analysis. Meanwhile, those that are included in the category of research recommendations that still do not have research are community service, learning process, learner, higher education, online learning environment.  The topic of community service makes a very positive contribution in creating a learning environment and of course the learning environment is not only directly manum but must also be done through learning in an online learning environment.